Challenges of nurses and care management of depressed older adults: a narrative literature review. Issue 3 (9th September 2020) - Albougami, Abdulrhman Saad B.; Almazan, Joseph U.; Stitt, Nancy; P. Cruz, Jonas; C. Colet, Paolo; Adolfo, Cris S.
Abstract : Background: The number of older adults with depression has increased in recent years. In relation to this, conducting a narrative review helps provide a better understanding of the adaptive functioning of depressed older adults and the significance of interventions in reducing depression. This narrative review investigates the nurses' management of depressed older adult patients. It also presents a detailed investigation of the barriers preventing nurses from successfully implementing nursing care for older adults. Methods: A narrative literature review was performed on four electronic databases, namely, (i) Cumulative Index of Nursing and Allied Health Literature, (ii) Pubmed, (iii) PsycINFO and (iv) Taylor and Francis. English language and peer‐reviewed journal articles were included. Results: A total of 19 articles were selected for the review, and four main themes were generated: (i) the challenges in implementing depression care management, (ii) the role of social support in depression treatment, (iii) the pharmacological management approach and (iv) the health care management process. Conclusion: Nurses experience several challenges in implementing depression care management. The role of social support in the treatment of depression, pharmacological management and different types of health care management strategies all provide solutions for depressed older adults. The review findings provide insights for improving health care nursing services for depressed older adults and reducing the negative health outcomes in this population.